Enhanced carrier mobility and thermoelectric performance in Cu2FeSnSe4 diamond-like compound via manipulating the intrinsic lattice defects. (December 2018) - Song, Q.; Qiu, P.; Chen, H.; Zhao, K.; Guan, M.; Zhou, Y.; Wei, T.-R.; Ren, D.; Xi, L.; Yang, J.; Chen, Z.; Shi, X.; et al.
Abstract: Diamond-like compounds represent a large family of new high-performance thermoelectric (TE) materials that have been extensively studied since 2009. However, their carrier mobilities are usually low because of the severe intrinsic lattice defects. In this study, we show a successful example of optimizing the carrier mobility of quaternary Cu2 FeSnSe4 diamond-like compound by manipulating the intrinsic lattice defects. A series of Cu-rich Cu2+δ Fe1-δ SnSe4 (δ = 0, 0.025, 0.05, 0.075, and 0.1) samples have been prepared in experiment. The rich Cu atoms effectively suppress the formation of negatively charged Cu vacancy defects, which are the main intrinsic lattice defects in Cu2 FeSnSe4 according to the defect formation energy calculation. The reduction of Cu vacancy defects significantly weakens the ionized impurity scattering to the carriers, leading to the substantially increased carrier mobility and optimized electrical transport properties in these Cu-rich Cu2+δ Fe1-δ SnSe4 samples. Consequently, the dimensionless figure of merit of Cu2.1 Fe0.9 SnSe4 at 800 K is enhanced by 53% as compared with that of the stoichiometric Cu2 FeSnSe4 . This study also sheds light on the optimization of TE performance in other materials with similar severe intrinsic lattice defects. Graphical abstract: A successful example of optimizing the carrier mobility of quaternary diamond-like compound Cu2 FeSnSe4 is demonstrated in experiment by manipulating the intrinsic Cu vacancy defects. This study also sheds light on the optimization of thermoelectric performance in other materials with similar severe intrinsic lattice defects. Highlights: A successful example of optimizing zT in Cu2 FeSnSe4 by manipulating the intrinsic lattice defects is given. Defect formation energy calculation shows that Cu vacancies are the dominated intrinsic lattice defects in Cu2 FeSnSe4 . Ionized impurity scattering in Cu-rich Cu2 FeSnSe4 is weakened due to the reduction of Cu vacancy defects.